Analisis Dampak Pembebasan Tanah dan Nilai Ganti Rugi Terhadap Kondisi Sosial Ekonomi Masyarakat Dalam Pembangunan Waduk Logung di Desa Kandangmas dan Desa Tanjungrejo Kabupaten Kudus - Andriani Swela; Edi Santosa; Dzunuwanus Manar (Journal of Politic and Government Studies, 2017)
Land acqusition is always a special concern for people whose land is acquired since it always carries impacts in any construction project.  Likewise the land acquisition of Waduk Logung construction project in Kudus district, it is also impacted on socio-economic condition of society in Kandangmas and Tanjungrejo village who are affected by construction project. The purpose of this research is to identify and analyze the impacts which are produced by land acquisition and its compensation value from the Waduk Logung construction project. The research used a mixed method which uses sequential explanatory method. Sequential explanatory mix method is characterized with data collection and quantitative data analysis for the first stage, and followed by data collection and qualitative data analysis for the second stage in order to support the result of first stage. In obtaining data, the researcher use questionnaire instrument which is distributed to the people affected by the construction plan in Kandangmas and Tanjungrejo village. Besides, the researcher also used interview data from interviewees which are connected and secondary data which are coming from documents, mass medias, and other literature sources such books and journals. The result shows that there is an effect of the land acquisition and compensation values from the Waduk Logung project which provides impacts to the socio-economic condition of people which are affected to the project plan. The effects of the land acquisition and compensation values are, 1) Society anxiety, 2) Negative perseption which make horizontal conflict  and vertical conflict 3) Economic Impact like decrease in revenues, livelihood change, wealth level decrease, and education guarantee for familiy members of land right owners, 4) Environment Impact like decreasing air quality, noise, road damage, and decreasing some component of river hydrology. Based from the research, the impact that happen is caused by the influence of the process or the role of policy makers who do not comply with the rules.